2013
DOI: 10.5812/ircmj.3533
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Vaginal Lactobacilli Composition of Iranian Healthy and Bacterial Vaginosis Infected Women: A Comparative Analysis of Their Cytotoxic Effects with Commercial Vaginal Probiotics

Abstract: BackgroundVaginal flora of healthy women is dominated by Lactobacillus species which can prevent bacterial vaginosis.ObjectivesThe current study aimed to determine the differences in vaginal lactobacilli composition of Iranian healthy and bacterial vaginosis (BV) infected women and compared their cytotoxic effects with commercial vaginal probiotics.Patients and MethodsOne hundred and seventy eight vaginal specimens were collected from healthy and BV infected women. Lactobacillus colonies were obtained by cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…Acknowledging the relevance of HPV for cervical cancer development, probiotics could also be linked to cancer prevention. In this context, in vitro studies demonstrated that the combination of L. gasseri and L. crispatus present cytotoxic effect in HeLa cervical cancer cells naturally infected with HPV-18 and this effect did not occur in normal cervical cell lines [138,139]. An interventional study that recruited HPV-positive women with LSIL reported that patients treated with oral L. casei had a significantly higher chance of resolving cytological abnormalities compared to untreated women, yet both groups did not differ significantly with respect to HPV clearance [140] (Table 1).…”
Section: Probiotics and Microbiota Manipulationmentioning
confidence: 99%
“…Acknowledging the relevance of HPV for cervical cancer development, probiotics could also be linked to cancer prevention. In this context, in vitro studies demonstrated that the combination of L. gasseri and L. crispatus present cytotoxic effect in HeLa cervical cancer cells naturally infected with HPV-18 and this effect did not occur in normal cervical cell lines [138,139]. An interventional study that recruited HPV-positive women with LSIL reported that patients treated with oral L. casei had a significantly higher chance of resolving cytological abnormalities compared to untreated women, yet both groups did not differ significantly with respect to HPV clearance [140] (Table 1).…”
Section: Probiotics and Microbiota Manipulationmentioning
confidence: 99%
“…This species, along with L. crispatus , has also been shown to be cytotoxic to HPV-18-infected HeLa cervical cancer cells but not to normal cervical cell lines, independent of pH or lactate concentration, suggesting a more sophisticated mechanism of action [85, 118]. Furthermore, a semi-randomised, interventional study of 54 HPV-positive women with low-grade cervical lesions showed that women treated with oral L. caseii showed greater clearance of HPV infections (29 vs 19 %) and were significantly more likely to clear their cervical lesion (60 vs 31 %), compared to an untreated cohort [119].…”
Section: Probiotics Prebiotics and Hpvmentioning
confidence: 99%
“…The mechanism of action of lactobacilli seems to be strain specific (Otles et al, 2003). Lactobacillus crispatus and Lactobacillus acidophilus are among the most commonly occurring species in vagina of healthy women (Vásquez et al, 2002;Motevaseli et al, 2013b). Probiotic bacteria have shown to have antineoplastic functions (Meurman et al, 1995), but their exact mechanism of cell growth inhibition is not fully elucidated.…”
Section: Introductionmentioning
confidence: 99%